Mixed neuroendocrine non-neuroendocrine neoplasm of the gallbladder complicated by a pancreaticobiliary maljunction of a non-dilated biliary duct: A case report. Issue 39 (1st October 2021) - Wagatsuma, Kohei; Akita, Kotaro; Motoya, Masayo; Kimura, Yasutoshi; Sugita, Shintaro; Hirano, Takehiro; Kawakami, Yujiro; Numata, Yasunao; Ishigami, Keisuke; Masaki, Yoshiharu; Murota, Ayako; Shitani, Masahiro; et al.
Abstract: Rationale: Mixed neuroendocrine non-neuroendocrine neoplasm (MiNEN) is a rare tumor. MiNEN of the gallbladder (GB) with pancreaticobiliary maljunction (PMJ) is extremely rare. The origin of MiNEN of the GB remains unknown; the biliary tract normally lacks neuroendocrine cells. MiNEN of the GB has a poor prognosis; because of its rarity, no treatment or management guidelines have been established yet. Patient concerns: A 47-year-old male presenting with right hypochondrial pain and malaise for 3 months was referred to our hospital for further management. Diagnosis: The neuron-specific enolase level was increased. Contrast-enhanced computed tomography revealed a mass of 70 mm in size with unclear boundaries in the liver. The GB was surrounded by this mass, narrowing the lumen of the GB. Many swollen lymph nodes were observed in the hepatoduodenal ligament. Endoscopic retrograde cholangiopancreatography revealed a PMJ with a non-dilated biliary duct. A percutaneous biopsy was performed on the liver mass, and the pathological findings were neuroendocrine carcinoma (NEC) (small cell type). We diagnosed a NEC of the GB, T3N1M0, stage IIIB (Union for International Cancer Control, 7th edition). Interventions: Because of advanced lymph node metastasis, we considered this tumor difficult to cure solely by surgical intervention. After initial chemotherapy consisting of cisplatin and irinotecan, a marked reduction in both tumor and lymph node sizes enabled conversion surgery. The pathological diagnosis of the resected tumor was MiNEN consisting of NEC and adenocarcinoma. The primary lesion was the adenocarcinoma occupying the luminal side of the GB. As a postsurgical treatment, the patient received additional irradiation therapy to the common hepatic duct and liver stump because of positive surgical margins. Outcomes: At 13 months postoperatively, computed tomography findings revealed the appearance of a hypervascular liver tumor, and laboratory data showed increased serum neuron-specific enolase levels. Chemotherapy was unsuccessful, leading to the death of the patient 36 months from the date of diagnosis. Lessons: There are several reports on the development of MiNEN of the GB. In our case, a PMJ-related adenocarcinoma of the GB transdifferentiated into NEC. Further accumulation of cases is necessary to establish a treatment strategy for MiNEN of the GB.